2021
DOI: 10.1186/s12889-020-10119-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the play and learning environments of children under two years in peri-urban Lima, Peru: a formative research study

Abstract: Background Home-based interventions have potential for improving early child development (ECD) in low-resource settings. The design of locally acceptable strategies requires an in-depth understanding of the household context. In this formative research study, we aimed to characterize the home play and learning environments of children 6–23 months of age from low-income households in peri-urban Lima, Peru. Methods Drawing on the developmental niche … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…One possible contributing factor is the potential lack of exposure to structured learning environments and educational stimuli during the critical early years of development [26]. Early childhood education programs often provide a foundation for cognitive, social, and emotional development, and the absence of such experiences may hinder overall developmental progress [27, 28]. Moreover, disparities in socio-economic conditions, parental education levels, and access to resources could play a role [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible contributing factor is the potential lack of exposure to structured learning environments and educational stimuli during the critical early years of development [26]. Early childhood education programs often provide a foundation for cognitive, social, and emotional development, and the absence of such experiences may hinder overall developmental progress [27, 28]. Moreover, disparities in socio-economic conditions, parental education levels, and access to resources could play a role [28].…”
Section: Discussionmentioning
confidence: 99%
“…Early childhood education programs often provide a foundation for cognitive, social, and emotional development, and the absence of such experiences may hinder overall developmental progress [27, 28]. Moreover, disparities in socio-economic conditions, parental education levels, and access to resources could play a role [28]. Children who do not participate in early childhood education programs may face additional challenges related to family income, educational support at home, and overall household well-being [21, 29-31].…”
Section: Discussionmentioning
confidence: 99%
“…Formative research has informed the design of ECD interventions in low and middle income countries 12 15 21 22 28–34. However, few trials in sub-Saharan Africa reported using formative research or local community advisory boards in intervention design, and there has been little research exploring caregiver beliefs and perspectives on development and learning from birth 12 15 22 34–38.…”
Section: Introductionmentioning
confidence: 99%